Hallmarks of Quercetin Benefits as a Functional Supplementary in the Management of Diabetes Mellitus-Related Maladies: From Basic to Clinical Applications - Farhadi, Faegheh; Sharififar, Fariba; Jafari, Mandana; Rahimi, Vafa Baradaran; Askari, Nafiseh; Askari, Vahid Reza (Current Drug Metabolism, 2024)
Quercetin (QE), a particular flavonoid, is well known for its medicinal effects, including anti-oxidant, hypoglycemic, and anti-inflammatory effects. In this review, the findings of QE effects on diabetes STZ-induced, alloxan-induced, and its complications have been summarized with a particular focus on in vitro, in vivo, and clinical trials. Consequently, QE mediates several mechanisms, including ameliorating tumor necrosis factor (TNF)-α, nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), interleukin (IL)-1β, IL-8, and IL-10 expression, increasing insulin glucose uptake to inhibit insulin resistance. Moreover, QE stimulates insulin secretion and attenuates insulin resistance through various pathways, namely transient KATP channel, motivating peroxisome proliferator-activated receptor expression, increasing glucose transporter-4, and decreasing inducible nitric oxide synthase in skeletal muscle. QE has protective effects on the complications caused by diabetes, such as polycystic ovary syndrome, high-fat diet-induced obesity, diabetic-induced hepatic damage, vascular inflammation, nephropathy, and neuropathy.
Keywords: oxidative stress